Persons with profound intellectual disability and their right to sex. Issue 4 (21st April 2019) - Vehmas, Simo
Abstract: This article discusses sexuality and sexual rights of persons with profound intellectual and multiple disabilities. I will address the issue by reflecting on my own previous negligence about the issue, and unpack the ethics of sexuality of persons with profound intellectual disability in the light of ethnographic observation and interview data. I will discuss the significance of cognitive and communicative capacities as regards sexual rights as well as the boundaries of ethically justified facilitation of sex. I will also analyse the definition of sex and its ethical implications. Finally, I will offer some reflections on how we should consider more carefully in research the sexuality of persons with profound intellectual and multiple disabilities in order to enhance in practice their sexual fulfilment.